1985
DOI: 10.2307/440070
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sponsorship and Bill Success in U. S. State Legislatures

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Comparative Legislative Research Center is collaborating with JSTOR to digitize, preserve and extend access to Legislative Studies Quarterly. This research tests how increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 6 publications
0
29
0
Order By: Relevance
“…Our empirical results on Congress can be compared with those of Browne's (1985) on state legislatures. Browne finds the following variables of importance: the sponsor's party affiliation, whether or not the sponsor sits on the committee that considers the bill, whether or not the sponsor chairs the committee that considers the bill, and the number of cosponsors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our empirical results on Congress can be compared with those of Browne's (1985) on state legislatures. Browne finds the following variables of importance: the sponsor's party affiliation, whether or not the sponsor sits on the committee that considers the bill, whether or not the sponsor chairs the committee that considers the bill, and the number of cosponsors.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason we did not feel it necessary to include this variable. Browne (1985) finds three variables, other than those we consider, to be important: the party affiliation of the sponsor, whether or not the sponsor sits on the committee that considers the bill, and the number of cosponsors. We tested the importance of the first two variables by including them in our regression model.…”
Section: Robustness Checksmentioning
confidence: 99%
See 1 more Smart Citation
“…Wilson and Young (1997) find that in the US Congress, co‐sponsorship increases the chances a bill passes, although only at the margins. Using data from the state legislatures of Florida, Michigan, Iowa and New Jersey between 1956 and 1978, Browne (1985) finds that bills with eight or more sponsors are about three times as likely as other bills to become law.…”
Section: Determinants Of Legislative Successmentioning
confidence: 99%
“…Although these studies have tended to focus on the short-term effects of experiencing power in laboratory settings, Winter and colleagues (1988;1985) have demonstrated that socialization experiences at earlier stages in life can influence how people orient and respond to changes in power much later in their lives. Thus, extrapolating these arguments to the domain of imprinting, we posit that the imprints acquired at the time of entry to a new institutional setting will be activated and expressed when a person later gains or loses structural power within that setting.…”
Section: Imprinting and Influencementioning
confidence: 99%